Perhitungan Dinding Penahan Tanah Sta 1+575- 1+700 Pada Ruas Jalan Durian Pata-Hitu - Selang, Taher; Titaley, Henriette Dorothy; Nanlohy, Ansye (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Roads are public facilities that are very much needed by the community. Various important activities in the use of roads as a means of transportation and mobilization. It is known that a landslide occurred on the Hulung Hamlet slope with STA 1 + 575- 1 + 700 km, on July 8, 2022 at 19.00 WIT with a width of 8 m, and a height of 12 m, the type of soil is sandy clay, the type of landslide is an arc landslide, which occurs due to high rainfall. The landslide disrupts the activities of road users because most of the material covers the road body and causes narrowing of the road body. And disrupts traffic on the left and right lanes of the road. One way used to control landslides is to stabilize the soil by building retaining walls. The methods used are literature studies, observations and testing of soil samples to find soil property data. Based on the test results, the soil property data obtained were clayey sandy soil type, with a water content of 24.60%, bulk density with a wet soil volume weight of 1.84 gr/cm3 and for a dry soil volume of 1.31 kg/cm3, a specific gravity of 2.59 Gs, a liquid limit (LL) of 44.7%, a plastic limit (PL) of 22.22% and a plastic index (IP) of 22.48%, the maximum dry volume weight of the soil sample tested was 1.316 gr/cm3 and its optimum water content (W optimum) was 12.67%, and the shear angle used was 30˚ and 5 KN/m2. With the design of a gravity-type terraced retaining wall, namely on plane 1 with an overall height of 5 meters and a foot width of 2.5 meters, namely for a rolling force of 2.6 (Safe), a shear force of 3.6 (Safe), the calculation of the ultimate support of 117.31 and for checking the safety factor is 3.86 (Safe), and in field 2 with an overall height of 4 meters and a foot width of 2.4 meters, namely for the overturning force of 3.8 (Safe), shear force of 5 (Safe), the calculation of the ultimate bearing capacity is 89.835 and for checking the safety factor is 3.8 (Safe).